2009
DOI: 10.1111/j.1365-2249.2009.03931.x
|View full text |Cite
|
Sign up to set email alerts
|

Naturally acquired inhibitory antibodies toPlasmodium vivaxDuffy binding protein are short-lived and allele-specific following a single malaria infection

Abstract: SummaryThe Duffy binding protein of Plasmodium vivax (DBP) is a critical adhesion ligand that participates in merozoite invasion of human Duffy-positive erythrocytes. A small outbreak of P. vivax malaria, in a village located in a non-malarious area of Brazil, offered us an opportunity to investigate the DBP immune responses among individuals who had their first and brief exposure to malaria. Thirty-three individuals participated in the five crosssectional surveys, 15 with confirmed P. vivax infection while re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
77
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 39 publications
3
77
0
Order By: Relevance
“…Similar patterns of immune selection have been observed with other microbial adhesion molecules such as the influenza hemagglutinin (HA) (15,35). Therefore, consistent with this immune escape paradigm for microbial pathogen ligands is a concern that variation found in the DBPII may lead to strain-specific immunity, thereby reducing the effectiveness of any anti-DBP immune response (6,19,31).…”
mentioning
confidence: 67%
“…Similar patterns of immune selection have been observed with other microbial adhesion molecules such as the influenza hemagglutinin (HA) (15,35). Therefore, consistent with this immune escape paradigm for microbial pathogen ligands is a concern that variation found in the DBPII may lead to strain-specific immunity, thereby reducing the effectiveness of any anti-DBP immune response (6,19,31).…”
mentioning
confidence: 67%
“…Formation of tight junction and invasion of human erythro- cytes by P. vivax require the interaction of PvDBP with the Duffy antigen on the erythrocyte (4,40,41). Recent reports in Madagascar showed that genetically diverse isolates of P. vivax can cause both asymptomatic and symptomatic vivax malaria and show frequent transmission even in the Duffy-negative population (5, 6), suggesting that P. vivax, similar to P. knowlesi (42,43) and P. falciparum (3), can use an alternative pathway(s) to invade erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Antibody responses to PvDBP have been shown in endemic populations of P. vivax infection in Papua New Guinea, [23][24][25] Brazil, [26][27][28] and Colombia. 29 In addition, different studies suggested that stronger humoral and cellular immune responses to PvDBP-II develop progressively with increasing age, 22,24,29,30 showing a boosting effect that was likely because of repeated exposures to the infection.…”
Section: Introductionmentioning
confidence: 99%